114k views
1 vote
A. Simplify the expression below.

1 + (-5)(5)(-2)

B.Simplify the expression below
(1 + -5)(5)(-2)

C.Simplify the expression below
[1 + -5(5)] (-2)

D. Simplify the expression below
-18
——-
-9+7

A. Simplify the expression below. 1 + (-5)(5)(-2) B.Simplify the expression below-example-1

1 Answer

5 votes

Answer:

(A). +51

(B). +40

(C). +48

(D). 9/8 or 1.125

Explanation:

(A) 1+50. =51

(B). (-4)(5)(-2) = 40

(C). (1 -25)(-2) = (-24)(-2) = 48

(D). 9/8

User Sandeep Giri
by
4.9k points